Profound and persistent painful paclitaxel peripheral neuropathy in a premenopausal patient. (10th May 2011) - Quintyne, K I; Mainstone, P; McNamara, B; Boers, P; Wallis, F; Gupta, R K
Abstract : The authors herein report the case of a 35-year-old woman undergoing adjuvant therapy for node positive breast cancer, who presented with short and rapidly progressive history of bilateral lower limb symptoms of peripheral neuropathy following therapy with paclitaxel. MRI of her neural axis revealed no leptomeningeal enhancement or focal metastatic lesions. Neurophysiological tests favoured toxic sensory axonal polyneuropathy. She remains symptomatic following discontinuation of therapy 20 months ago, and is under review with pain management.